2009
DOI: 10.3201/eid1509.090794
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiologic Characteristics of 3 Early Cases of Influenza A Pandemic (H1N1) 2009 Virus Infection, People’s Republic of China, 2009

Abstract: A national network is essential for controlling this infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 7 publications
0
41
0
Order By: Relevance
“…Severe influenza virus infection in humans with H5N1 and 2009 H1N1 viruses has been associated with leukopenia, lymphopenia, and thrombocytopenia; these clinical characteristics have not been consistently observed among mild cases of 2009 H1N1 virus infection in humans (4,37,39). Highly virulent viruses, including the reconstructed 1918 virus and the H5N1 virus used in this study, have previously been shown to result in peripheral blood lymphopenia in the mouse model (24,33).…”
Section: Discussionmentioning
confidence: 99%
“…Severe influenza virus infection in humans with H5N1 and 2009 H1N1 viruses has been associated with leukopenia, lymphopenia, and thrombocytopenia; these clinical characteristics have not been consistently observed among mild cases of 2009 H1N1 virus infection in humans (4,37,39). Highly virulent viruses, including the reconstructed 1918 virus and the H5N1 virus used in this study, have previously been shown to result in peripheral blood lymphopenia in the mouse model (24,33).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 22 individual articles (15 cohort studies involving >10 patients [4][5][6][7][8][11][12][13][14][15][16][17][18][19][20], 5 cohort studies involving up to 10 patients [21][22][23][24][25] and 2 case reports [26,27]) were regarded as eligible for inclusion in the review. Nine of these studies referred to the USA [5,8,13,16,17,20,21,23,24], two to Mexico [7,12], two to Canada [11,26], three to European countries (UK [6], Spain [14] and Cyprus [19]), two to China [25,27] and the remaining to Argentina [15], Australia and New Zealand [4], Japan [18] and Singapore [22].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nine of these studies referred to the USA [5,8,13,16,17,20,21,23,24], two to Mexico [7,12], two to Canada [11,26], three to European countries (UK [6], Spain [14] and Cyprus [19]), two to China [25,27] and the remaining to Argentina [15], Australia and New Zealand [4], Japan [18] and Singapore [22]. In addition, 7 of the 20 included cohort studies and case series were prospective [4,11,15,16,18,22,25], whereas the remaining 13 were retrospective [5][6][7][8][12][13][14]17,[19][20][21]23,24]. Regarding the 15 cohort studies involving >10 patients, 5 involved mainly ICU patients [4,[11][12][13][14], 6 involved mainly hospita...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…According to the Chinese Ministry of Health, approximately 197,000 suspected cases of influenzalike illness (ILI) were observed during the 2009-2010 flu season (http://www.cnic.org.cn/eng) with a considerably high proportion of hospitalizations, ICU admissions, and deaths [5][6][7][8]. However, available data, mostly based on case reports and retrospective analyses, portray the clinical picture of cases as situated in urban areas of the country, especially in Beijing and Shanghai, which are more likely to have been affected by international travel and do not represent a large portion of the Chinese population [4,[6][7][8][9][10][11][12]. Southern parts of mainland China, where Shantou and Nanchang are located, represent smaller urban centers more than the typical Chinese demographics.…”
Section: Introductionmentioning
confidence: 99%
“…China declared its first few cases of pH1N1 infection in May 2009 [4] and these were followed by a rapid transmission of infection in the community. According to the Chinese Ministry of Health, approximately 197,000 suspected cases of influenzalike illness (ILI) were observed during the 2009-2010 flu season (http://www.cnic.org.cn/eng) with a considerably high proportion of hospitalizations, ICU admissions, and deaths [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%